Research of the role of microstructure in the wear mechanism of canine and bovine enamel. (April 2019) - Xiao, Heng; Lei, Lei; Peng, Jiapin; Yang, Dan; Zeng, Qihang; Zheng, Jing; Zhou, Zhongrong
Abstract: The relationship between the microstructure and tribological behavior of mammalian tooth enamel has not been fully understood. In this paper, the microstructure, mechanical properties, and tribological behavior of canine (carnivore) and bovine (herbivore) enamel are studied using scanning electronic microscopy and nano-indentation/scratch technique, aiming to reveal the contribution of enamel microstructure to its mechanical and tribological properties. Canine enamel has a microstructure of hard keyhole-like rods embedded in soft inter-rod enamel, and its surface exhibits high resistance against both micro-crack initiation and crack-induced delamination during friction and wear process. Bovine enamel with the microstructure consisting of the hydroxyapatite (HAP) nano-fibers in decussation has higher surface hardness and better capabilities of resisting wear and encumbering crack propagation, as compared to canine enamel. In sum, the soft inter-rod enamel in the canine enamel contributes to high load tolerance and then protects enamel surface from brittle damage, while the staggered arrangement of HAP nano-fibers benefits hard bovine enamel in crack propagation resistance and then help resist wear and fatigue. The findings suggest that there exists a self-adaptation in enamel microstructure and tribological performance of mammals with their feeding habits, which will promote and assist the bionic design of high-performance materials. Graphical abstract: fx1 Highlights: Canine enamel has high resistance against microcrack initiation and brittle damage. Bovine enamel surface with high hardness has good crack propagation resistance. Soft inter-rod enamel contributes to the high load tolerance of enamel. HAP nano-fibers in decussation benefit hard enamel in crack propagation resistance. There exists self-adaptation in enamel microstructure and tribological performance.